2022
DOI: 10.1063/5.0088177
|View full text |Cite
|
Sign up to set email alerts
|

Toward machine learning for microscopic mechanisms: A formula search for crystal structure stability based on atomic properties

Abstract: Machine-learning techniques are revolutionizing the way to perform efficient materials modeling. We here propose a combinatorial machine-learning approach to obtain physical formulas based on simple and easily accessible ingredients, such as atomic properties. The latter are used to build materials features that are finally employed, through linear regression, to predict the energetic stability of semiconducting binary compounds with respect to zinc blende and rocksalt crystal structures. The adopted models ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In addition to melting point and crystal habit prediction, machine learning has been explored in the prediction of a number of other crystal properties. Some results have been achieved in predicting the stability of crystal structures. Using only two descriptors, namely Pauling electronegativity and ionic radius, Ye et al can predict the density functional generation energy of C 3 A 2 D 3 O 12 garnet and ABO 3 perovskite with an average absolute error of 7–10 meV/atom and 20–34 meV/atom, respectively, which are within the limits of density functional accuracy. A critical gap in the extension of machine learning models from fixed stoichiometric ratio crystals to the realm of infinite mixture crystal systems has been addressed.…”
Section: Crystal Properties Predictionmentioning
confidence: 99%
“…In addition to melting point and crystal habit prediction, machine learning has been explored in the prediction of a number of other crystal properties. Some results have been achieved in predicting the stability of crystal structures. Using only two descriptors, namely Pauling electronegativity and ionic radius, Ye et al can predict the density functional generation energy of C 3 A 2 D 3 O 12 garnet and ABO 3 perovskite with an average absolute error of 7–10 meV/atom and 20–34 meV/atom, respectively, which are within the limits of density functional accuracy. A critical gap in the extension of machine learning models from fixed stoichiometric ratio crystals to the realm of infinite mixture crystal systems has been addressed.…”
Section: Crystal Properties Predictionmentioning
confidence: 99%
“…The ions lose energy during their passage through the material, which is either spent in displacing the target atoms by elastic collision (nuclear stopping) or exciting the atoms by inelastic collisions (electronic stopping) . A large variety of studies exists on ion-beam induced modifications in magnetic ML, either in the context of patterning or depth-resolved structural modifications. , The creation of graded anisotropy media by domain wall positioning has also been reported using ion irradiation . Ion-induced modification of magnetic properties with depth-resolved structural studies in Co/Pt ML has been reported. , An interesting study on the investigation of magnetic domains after ion beam irradiation was performed by Trassinelli et al, where local microscopic features of domains were highlighted in the vicinity of the ferromagnetic to paramagnetic phase transition temperature for Mn–As thin films .…”
Section: Introductionmentioning
confidence: 99%
“…28 A large variety of studies exists on ion-beam induced modifications in magnetic ML, either in the context of patterning 29 or depth-resolved structural modifications. 30 , 31 The creation of graded anisotropy media by domain wall positioning has also been reported using ion irradiation. 32 Ion-induced modification of magnetic properties with depth-resolved structural studies in Co/Pt ML has been reported.…”
Section: Introductionmentioning
confidence: 99%